Perfil epidemiológico dos pacientes com câncer de próstata encaminhados a um hospital público e de atenção terciária no sul do Brasil - Löbler, Ricardo (2013)
Introduction: Prostate cancer is the most diagnosed cancer in males in Brazil. As it has a relatively indolent evolution and effective screening, patients with localized disease should be referred to the referral centers to perform treatment with curative intent. This study aimed to determine at what stage of the disease patients with prostate cancer are referred to tertiary care and regional referral public hospital for cancer treatment and how these cases were conducted. Methodology: This study included patients diagnosed with prostate cancer from the year 2000 to 2006. They were referred to the University Hospital of Santa Maria (HUSM). The data were described in prevalence percent, being used the Chi Square and Fisher tests, according to application; logistic regression was used to describe potential risk factors, the prevalence ratio was calculated by a non-parametric generalized regression model, using the Poisson distribution, significant statistical difference was considered when p <0.05. Excel 2007 was used to tabulate the data and the analysis was performed using version 18.0 IBM statistical program SPSS for Windows. Results (Article 1): 240 patients with prostate cancer were referred to HUSM during the years 2000 and 2006, of which 59.6% had localized disease, 25% had metastatic disease, and 15.4% had biochemical recurrence. Considering the 143 patients with localized disease, 34.3% were treated with radical prostatectomy, 33.6% with radiotherapy, 20.2% underwent palliative treatments, and 11.9% were under observation. The causes associated with not performing curative treatment of patients with localized disease were: undetermined in 32.6% of the cases, problems due to delay in hospital care in 30.4% of the cases, locally advanced disease in 21.7% of the cases, high surgical risk in 13.1% of the cases, and other reasons in 2.2% of the cases. Of the patients who were referred with localized disease, 20.2% underwent palliative treatments and 11.9% were under observation; in this situation, approximately, one third of the patients with localized disease did not undergo curative treatment due to delay in the waiting list for surgery and, in one third of the cases, the cause was not defined in the medical charts, showing that medical reports were not adequately filled in. Results (Article 2): In patients with localized prostate cancer treated with radical prostatectomy, biochemical recurrence occurred in 34 of 47 patients (72.3%). In this sample, unlike what is described in the literature, there was no correlation between risk ratings and possible risk factors (age, Gleason score, PSA level at diagnosis, T stage) with biochemical recurrence. Conclusions: In comparison with the Medical Literature, there were a greater number of patients referred to a referral hospital with metastatic disease, a lower proportion of patients undergoing curative treatment and less use of radical prostatectomy as a curative treatment. Regarding patients who were treated with radical prostatectomy, there was a higher prevalence of biochemical recurrence.